It's a long story [compact disc, unabridged] : my life - Nelson, Willie, 1933-; Ritz, David (Blackstone Audio, Inc. ; Hachette Audio, 2015)
This is the unvarnished, complete story of Willie Nelson's life, told in his distinct voice and leaving no moment or experience unturned, from Texas and Nashville to Hawaii and his legendary bus. Having recently turned eighty, Nelson is ready to shine a light on all aspects of his life, including his drive to write music, the women in his life, his collaborations, and his biggest lows and highs--from his bankruptcy to the founding of Farm Aid. An American icon who still tours the country and headlines music festivals, Willie Nelson and his music have found their way into the hearts and minds of fans the world over, winning ten Grammys and receiving the Kennedy Center Honors. Now it's time to hear the last word about his life--from the man himself.